Andrea Camilleri and History - Sciarrone, Roberto (Mediterranean Journal of Social Sciences, 2012)
The historical novel and Andrea Camilleri. A marriage that takes place through works by several different periods ofmodern history and contemporary, the unification of Italy, Sicily in the Eighteenth century, the Fascist period, today's world. TheSicilian writer, ironically, many environmental novels in the important moments of our national history, with particular attention tothe problems of the south. The gap between North - South and industrialized - backlog characterizes much of his historicalnovels, continuing his studies of Pasquale Villari (1827 - 1917), among the first historians interested in the phenomenon. Sicily,when he was a kingdom without a crown, had dreamed of a place in Europe. Now, fifty years from Unity, must fight to keep hisplace in Italy. Even a hundred years later, today, the problem not only of Sicily, but throughout the South is still a problem.